Acute exercise is associated with specific executive functions in college students with ADHD: A preliminary study - Jennifer I. Gapin; Jeffrey D. Labban; Sara C. Bohall; Joshua S. Wooten; Yu-Kai Chang (Elsevier, 2015)
Purpose: The relationship between acute exercise and executive functions in college students with attention deficit hyperactivity disorder (ADHD) has not been clearly established. The purpose of this preliminary study was to examine the difference in cognitive performance between college students with and without ADHD and to explore the effects of acute exercise on multiple aspects of executive functions and on serum brain derived neurotrophic factor (BDNF). Methods: College students (normal: n = 10; ADHD: n = 10) performed the Stroop Test, Trail Making Test, and Digit Span Test prior to and after an acute exercise intervention. Blood samples were obtained prior to the pre-test cognitive test performance and then again after exercise and prior to the post-test cognitive test performance. Results: Students with ADHD exhibited impaired executive functions, particularly on inhibition. Additionally, while acute exercise improved all aspects of executive functions in those without ADHD, acute exercise only improved inhibitory performance for those with ADHD. Further, BDNF was not influenced by acute exercise regardless of the subjects' ADHD status. Conclusion: These results provide preliminary evidence for exercise as a potential adjunct treatment for benefitting inhibition in college students with ADHD.